Association between periodontitis and pulmonary function based on the Third National Health and Nutrition Examination Survey (NHANES III). (25th May 2020) - Lee, Wei‐Cheng; Fu, Earl; Li, Chung‐Hsing; Huang, Ren‐Yeong; Chiu, Hsien‐Chung; Cheng, Wan‐Chien; Chen, Wei‐Liang
Abstract: Objectives: The purpose of this study was to investigate the association between impaired pulmonary function and periodontitis. Materials and Methods: From the Third National Health and Nutrition Examination Survey data, we examined the association between pulmonary function and severity of periodontitis using the univariate and multivariate regression models. Moreover, the association between obstructive or restrictive spirometry patterns and periodontitis status was also determined by multivariable logistic regression analysis. Results: A total of 10, 645 participants were included in our study. The values of predicted FEV1%, predicted FVC%, and FEV1/FVC were found to gradually decline with increasing severity of periodontitis ( p < .001). Obstructive and restrictive pulmonary functions were significantly associated with severity of periodontitis. Conclusion: Individuals with a greater degree of periodontitis had poor pulmonary function. However, further long‐term cohort studies are required for a comprehensive evaluation.